2015
DOI: 10.1093/gbe/evv067
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Variability of Domestic River Buffalo (Bubalus bubalis) Populations: Genetic Evidence for Domestication of River Buffalo in Indian Subcontinent

Abstract: River buffalo, Bubalus bubalis is a large bovine species frequently used livestock in southern Asia. It is believed that the river buffalo was domesticated from Bubalus arnee, the wild buffalo of mainland Asia, a few thousand years ago, probably during the period of Indus Valley civilization. However, the domestication history of the river buffalo has been the subject of debate for many decades mainly due to the lack of clear archeological evidence and the divisive conclusions of the genetic studies. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 16 publications
3
29
0
Order By: Relevance
“…S3, Supporting information, Nagarajan et al . ) indicates a phylogeographic structure of the maternal lineages of river buffalo that is weaker than observed for cattle (Lenstra et al . ), sheep (Cai et al .…”
Section: Discussionmentioning
confidence: 98%
“…S3, Supporting information, Nagarajan et al . ) indicates a phylogeographic structure of the maternal lineages of river buffalo that is weaker than observed for cattle (Lenstra et al . ), sheep (Cai et al .…”
Section: Discussionmentioning
confidence: 98%
“…123 Temporal and geographical information comes from Pearsall 124. , Clement et al 125 130 . 131 have shown that the area that our figure shows was subject to intensive land use for several centuries between the 8 th and 12 th centuries CE, punctuated by episodes of severe erosion.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…in Pakistan, India, Egypt and the Mediterranean; Hassan et al ; Babar et al ; Mishra et al ), and further suggested that the post‐domestication migration from the Indian subcontinent towards western Asia and Europe took place gradually and without substantial population bottlenecks (Zhang et al ). Further mtDNA evidence also pointed to a repeated incorporation of wild buffalo mtDNA variants into the Indian domestic stocks following domestication (Nagarajan et al ). As has been done for swamp buffaloes (Wang et al ), extending the evaluation of river buffalo mitochondrial diversity to the whole mtDNA genome should provide a better understanding of river buffalo domestication and dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…Divergence of the two types clearly preceded their domestication, as molecular evidence (Kumar et al ; Nagarajan et al ) indicates domestication of the river buffalo in the western region of the Indian subcontinent around 6.3 kyr BP, and of the swamp buffalo in the China/Indochina border region (Zhang et al , ; Wang et al ), with a time of domestication of 3–7 kyr BP (Wang et al ). Domestication of both types was followed by a rapid expansion of their population sizes (Finlay et al ; Wang et al ), partly owing to the improving climatic conditions during the Holocene post‐glacial phase and also to the geographical spread of domesticated animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation